The effect of teaching by using drama method on the acquisition of eighth grade students of human rights concepts included in the National Education textbook in Al- Karak governorate - Al-Haraki, Omar Abdullah (Arab Journal for Sciences and Research Publishing, 2017)
This study aimed at investigating the impact of teaching by the method of drama on helping the students of the basic eighth-grade to acquire the concepts of human rights included in the National Education textbook. The study sample consisted of 48 students of the basic eighth grade in the model school at Mu'tah University. The study was conducted on the two groups; the control group which studied according to the method usual, and the experimental which was taught by using the method of drama, and the test was used as the instrument for measurement. The study concluded that the arithmetic mean for the performance of the students, who studied human rights concepts by
Keywords: The Drama Method; Human Rights Concepts; Acquisition; Eighth Grade Students